تأثير ابتكار مدرس اللغة العربية نحو الجاز تعلمها التلاميذ - Najib, Aan; Junaedi; Fahmi, Zain Hendra; Kafilah, Nur (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
In the educational process there are various problems associated with it. One of the obstacles is that some teachers may use teaching methods and means of explanation that are not in accordance with the material they provide or the different conditions of students. These problems will cause a decrease in the quality of education and will ultimately lead to a decrease in the learning achievement of male and female students. This study was conducted to determine the innovation of the first grade Arabic teacher at Madrasah Ibtidaiyah Buduran-Sidoarjo, and to determine the Arabic learning achievement of the first graders of Madrasah Ibtidaiyah Buduran-Sidoarjo. This study uses a quantitative approach. This research demands the use of digital in terms of collecting facts, analyzing data, and displaying data acquisition. Sources of research data obtained by researchers from two sources, namely library data and field data. This research can show that in the learning process teachers should use appropriate methods for students. Previously, teachers had to look at students’ situations where there were differences between them, and about the proper way to apply them in their learning. School innovation affects the quality of education and student educational achievement. School innovation affects the quality of education as well as learning achievement. If school innovation and quality of education are good, then the educational achievement of students is also good.